It matters whether reading comprehension is conceptualised as rate or accuracy. (27th March 2015) - Rønberg, Louise Flensted; Petersen, Dorthe Klint
Abstract : This study shows that it makes a difference whether accuracy measures or rate measures are used when assessing reading comprehension. When the outcome is reading comprehension accuracy (i.e., the number of correct responses), word reading skills (measured as access to orthographic representations) account for a modest amount of the variance in the reading comprehension of 10‐year old children. However, this changes when reading comprehension is conceptualised as rate (i.e., number of correct responses per minute); when this is done, the correlation with word reading increases. The result was validated in two different reading comprehension tests. Moreover, this study indicates that it is not merely efficient word reading that influences the process of comprehending at a fast rate. When word reading and receptive vocabulary are controlled, a written measure of the ability to access and connect similar word meanings (synonym judgement) explains additional variance in reading comprehension rate.